2008
DOI: 10.1111/j.1365-2842.2007.01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the use of full dentures and mucosal alterations among elderly Brazilians

Abstract: The objective of the present study was to evaluate the prevalence of oral mucosal lesions associated with the use of full dentures (FD) among non-institutionalized individuals of 60 or more years of age in a rural Brazilian population. The sample consisted of 344 individuals aged 60 or more from two rural communities of Brazil. Of this total, 146 were FD users and 198 FD, non-users. Angular cheilitis, denture stomatitis and inflammatory fibrous hyperplasia were statistically associated with prosthesis use. Hyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
2
23

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 16 publications
(17 reference statements)
6
73
2
23
Order By: Relevance
“…These results indicate that PDW, especially those with acrylic base, have similar trends of developing lesions when compared to complete dentures. This study showed that there was a greater frequency of DML as length of denture use increased, in contrast with previous studies (5,8). According to Moskona and Kaplan (12), the length of denture use increases with the increasing of age, since older patients are reluctant to restore or to replace old dentures, which can cause oral lesions.…”
Section: Discussioncontrasting
confidence: 82%
“…These results indicate that PDW, especially those with acrylic base, have similar trends of developing lesions when compared to complete dentures. This study showed that there was a greater frequency of DML as length of denture use increased, in contrast with previous studies (5,8). According to Moskona and Kaplan (12), the length of denture use increases with the increasing of age, since older patients are reluctant to restore or to replace old dentures, which can cause oral lesions.…”
Section: Discussioncontrasting
confidence: 82%
“…7,8 Buna bağlı olarak, oral mukoza lezyonlarının sıklığının hareketli protez kullanan hastalarda, kullanmayanlardan fazla olduğu çeşitli çalışmalarda bildirilmiştir.…”
Section: Introductionunclassified
“…This study concluded 82% of dental practitioners had knowledge and attitude Dentures can cause oral mucosal lesions that could be prevented with poston the principles of taking an adequate history, clinical related mucosal lesions have been associated with denture plaque, Candida infection, poor denture retention and mechanical trauma. [13][14] Dentures may predispose patients to the onset of mucosal lesions such as candidiasis, inflammatory or reactive hyperplasia and…”
Section: Among Dental Practitioners Regarding Management Of Denture Imentioning
confidence: 99%